A Study on Job Satisfaction of Women Workers in Tea Estates With Special Reference to the Nilgiris District - Amsaveni, R.; Ilavarasi, J.; Gomathi, S. (Prabandhan: Indian Journal of Management, 2013)
Job satisfaction is an important indicator of how workers feel about their jobs and is a predictor of work behaviors. The study aimed to ascertain the job satisfaction levels of women workers employed in tea estates located in the Nilgiris District, Tamil Nadu. The Nilgiris being the largest tea tract in South India occupies an important place in the tea map of the country. Thus, tea plays a vital role in the economy of the district. Therefore, an attempt has been made in the present paper to identify the problems faced by the women workers, examine the facilities offered to them, and ascertain the satisfaction level of the women workers in tea estates in the Nilgiris district. The data was collected through a structured interview schedule from 300 respondents by using the convenience random sampling method. The tools used for analysis, that is, simple percentage, chisquare analysis, and factor analysis were applied to analyze the collected data. The results of the study revealed that there was a significant relationship between the demographic factors and the health related problems faced by the women workers. Furthermore, the findings show that the majority of the respondents were illiterate, and were employed in the process of plucking the tea leaves, as this activity generates a major chunk of the revenue for the tea estates. From the factor analysis, it was identified that the factors such as Work Allotment and Relationship with Colleagues, Support and Reward, Safe Environment, Compensation, and Training and Development influenced the levels of job satisfaction significantly. In addition, it was also found that four factors, that is, Disability, Workplace Environment, Pay and Conveyance, and Work Timings were the highly problematic factors causing dissatisfaction among the women workers employed in the tea estates.